Welfare impact of social breeding value and straw for growing-finishing pigs - Jacobs, Leonie (SLU/Dept. of Animal Environment and Health (until 231231), 2012)
Animal welfare is of increasing concern in present society. In commercial pig farming, animal welfare problems are common. One of the causes for these problems is the barren environment in which pigs are housed, which can cause oral manipulation of pen mates. Providing straw might be one solution to this problem. Another solution could be reached through genetic selection. Present breeding schemes are only focused on direct production characteristics of the individual, like growth performance. Welfare, as well as production, might be improved by including the effect an animal has on its pen mates in the selection criteria. However, effects on welfare of selection for the so called Social Breeding Value (SBV), which is based on growth, are largely unknown. This study investigated the direct welfare effects induced by straw as well as SBV and the possible interaction between both. In a one generation selection experiment, 192 finishing pigs with either a high or low SBV, were housed in barren or straw pens. In this 2x2 experimental design, pigs were studied from weaning until slaughter. Welfare status was assessed using a protocol that was partly based on the Welfare Quality® protocol. Results show that straw had a positive welfare effect regarding tail biting and exploration. Straw housed pigs had less infections and greater body weight at slaughter age than barren housed pigs. Pigs in enriched pens did show more lesions than barren housed pigs, probably due to raised overall activity in enriched pens. No welfare effect was found due to SBV, besides an effect on the occurrence of a rough hair coat. No interactions were found. It can be concluded that the welfare impact of SBV for growing-finishing pigs is not yet proven.